Expanded Fetal Growth Restriction Definition Identifies High Proportion of Umbilical Artery Doppler Anomalies - Nakahra, Angela; Long, Miranda; Elmayan, Ardem; Biggio, Joseph R.; Williams, Frank B. (American Journal of Perinatology, 2024)
Objective Fetal growth restriction (FGR) increases the risk for perinatal morbidity and mortality. The Society for Maternal-Fetal Medicine expanded the definition of FGR to independently include abdominal circumference (AC) < 10th percentile for gestational age (GA), regardless of estimated fetal weight (EFW). While studies have shown increased detection of small for GA neonates with expanded definition, no studies have evaluated the likelihood of abnormal umbilical artery Dopplers (UAD) detection with expanded definition. The objective of this study was to compare the likelihood of identifying UAD abnormalities in fetuses with normal EFW and restricted AC versus those by EFW alone.Study Design Single-institution retrospective cohort study of fetal growth ultrasounds meeting criteria for FGR either by EFW < 10th percentile or AC < 10th percentile with normal EFW. Those with FGR by AC alone were compared with those with FGR by EFW. Primary outcome was prevalence of UAD abnormalities, including elevated systolic/diastolic ratio, and absent and/or reversed end diastolic velocity. Receiver operator characteristic curves were generated to compare predictive value of UAD abnormalities by FGR definition.Results A total of 619 scans met criteria for FGR between November 2020 and June 2021, with 441 (71%) meeting definition by EFW and 178 (29%) by AC criteria alone. Baseline characteristics were similar between groups. FGR by AC alone was identified earlier (30.4 ± 3.3 vs. 35.4 ± 3.0 weeks' gestation, p < 0.001) with higher proportion identified before 32 weeks (70 vs. 11%, p < 0.001). Proportion of abnormal UAD were similar between groups (15 vs. 15%, adjusted odds ratio: 1.12, 95% confidence interval: 0.61–2.23). Use of EFW alone would have failed to identify 29% of abnormal UAD. A combined definition of FGR had the highest detection of abnormal UAD (area under curve: 0.78 vs. AC alone 0.73 vs. EFW alone 0.69).Conclusion A definition of FGR that considers both EFW and AC improves detection of abnormal UAD.Key Points
Keywords: fetal growth restriction; abnormal umbilical artery Doppler; estimated fetal weight; abdominal circumference; umbilical artery systolic to diastolic ratio